Estimating the cost efficiency and marginal cost of carbon reductions in the production of drinking water. (October 2022) - Molinos-Senante, Maria; Maziotis, Alexandros; Sala-Garrido, Ramon; Mocholí-Arce, Manuel
Highlights: Average marginal cost of reducing carbon emissions in water treatment facilities was 30 €/ton CO2eq . Drinking water treatment plants could save 61.4% of their operational costs. Size of facilities and source of raw water influence on the performance of facilities. Abstract: Access to safe, reliable and affordable drinking water is a human right that should be achieved without neglecting Sustainable Development Goal 13 of the United Nations related to climate action. The production of drinking water involves using a non-negligible amount of energy, leading to relevant economic costs and greenhouse gas (GHG) emissions. Here, we employed a parametric method to assess the cost efficiency of a sample of drinking water treatment plants (DWTPs) and to estimate the marginal cost of reducing GHG emissions. The average cost efficiency was 0.386, indicating that the evaluated DWTPs had notable room (61.4%) to save costs. The average marginal cost was estimated at 30€ per ton of CO2eq. When comparing this value with the current carbon costs of carbon trading systems, reducing the GHG emissions of DWTPs might be cost-effective. The parametric approach enabled us to evaluate the influence of several environmental variables on the cost efficiency and marginal cost of reducing GHG emissions. Specifically, the size of the facility and source of raw water significantly influenced DWTP performance. In conclusion, this study provides a novel tool to obtain insights on the water-energy nexus for informed decisions towards a more sustainable urban water cycle.